Microstructural evolution of pure magnesium under high strain rate loading. (1st April 2015) - Dixit, Neha; Xie, Kelvin Y.; Hemker, Kevin J.; Ramesh, K.T.
Abstract: The mechanical behavior of extruded pure magnesium was studied experimentally under high strain rate ( 10 3 s - 1 ) compression loading in the extrusion direction. Electron back scattered diffraction was used to examine the changes in the texture and transmission electron microscopy was used to investigate the dislocation structures in the material. Extensive grain reorientation due to extension twinning is observed. Dislocation activity is observed inside the parent region ( 〈 a 〉 slip) as well as the twinned region ( 〈 c + a 〉 slip). The high degree of strain hardening observed is postulated to be due to the texture hardening associated with extension twinning coupled with significant increase in the dislocation density with strain. In compression along the extrusion direction, extension twinning and dislocation activity are both needed to accommodate plastic deformation.